Po kos prava v regulativni peskovnik ali srečevanja nepredvidljive kreativne neodvisnosti in predvidljive pravne realnosti - Božič, Katja (Pravni letopis, 2023)
There is a new legal instrument within the framework of EU law - regulatory sandbox, which is rather unknown to the national legal order. Conceptually speaking, it is tightly related to so called experimental clauses, which enable the implementation of its substance and goals. Regulatory sandbox is meant to accelerate testing of innovative technological solutions in real life. The main driving force is awareness of traditional legal drafting processes not keeping up to date with technological development. Regulatory sandbox is somehow a combination of temporary exemptions from requirements, restraints and other legal rules in force when implementing (testing) new business models, services and products, based on new (innovative) technologies, when those solutions can not be implemented within the existing legal order, where, on the other side, traditional legal amendments would be eligible only after precedent testing and thorough optimization, including the basic risk management as to the amendments of legal framework in force.
Keywords: določbe o eksperimentiranju; pravo EU; regulativni peskovnik; tehnološke inovacije